INNOVATIVE TRANSFORMATIONS OF THE NATIONAL LEGAL SYSTEM OF UKRAINE AS A CONDITION FOR PARTICIPATION IN EUROPEAN POLICIES - Oleksandr Perederii (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The article highlights the essence of the main innovative transformations taking place in the legal system of Ukraine in the context of intensification of the European integration processes from the standpoint of general theoretical analysis. The author focuses on the interrelation between changes in the national legal system of Ukraine and the State's involvement in European policies.